The Role of Psychology in Investigations - Youngs, Donna; Zeyrek-Rios, Emek Yüce (The Bulletin of Legal Medicine, 2014)
The current paper will review the ways psychology, particularly Investigative Psychology, contributes to investigations. The three broad types of contributions are; investigative inferences, the investigation process and the assessment and improvement of investigative information. Psychology can provide useful decision support tools to facilitate the investigation processes and help investigators to give more appropriate decisions. The application of psychological principles is also beneficial in the evaluation process of the accuracy of the investigative information. Grounded on the actuarial evidence, psychology is able to generate answers to many questions raised in different stages of police investigations. Key words: Crime, Investigation, Profiling, Investigative Psychology.